# analytic geometry: equation of lines through one point and at a distance from another point

## New forum topics

- Please help me solve this problem: Moment capacity of a rectangular timber beam
- Solid Mensuration: Prismatoid
- Differential Equation: (1-xy)^-2 dx + [y^2 + x^2 (1-xy)^-2] dy = 0
- Differential Equation: y' = x^3 - 2xy, where y(1)=1 and y' = 2(2x-y) that passes through (0,1)
- Tapered Beam
- Vickers hardness: Distance between indentations
- Time rates: Question for Problem #12
- Make the curve y=ax³+bx²+cx+d have a critical point at (0,-2) and also be a tangent to the line 3x+y+3=0 at (-1,0).
- Minima maxima: Arbitrary constants for a cubic
- Minima Maxima: y=ax³+bx²+cx+d

## Create a circle of radius 1

Create a circle of radius 1 with center at (2, 1). The equation of the circle would be (x - 2)

^{2}+ (y - 1)^{2}= 1. Then draw a line through (7, -4) that is tangent to your circle, you can see that you can draw two such lines, one is above the (2, 1) and the other is below the point (2, 1). You only need to draw one of the lines. Call the point of tangency as (x_{1}, y_{1}) and our task now is to locate this point of tangency. You can find (x_{1}, y_{1}) knowing that this point is common to the circle and the line. Once you get (x_{1}, y_{1}), you have now two points on the line to be used to find its equation.## Here is the details of the

Here is the details of the solution:

$(x - 2)^2 + (y - 1)^2 = 1^2$

$(x^2 - 4x + 4) + (y^2 - 2y + 1) = 1$

$x^2 + y^2 - 4x - 2y + 4 = 0$

The circle above will pass through (x

_{1}, y_{1})${x_1}^2 + {y_1}^2 - 4x_1 - 2y_1 + 4 = 0$ ← Equation (1)

Equation of tangent to x

^{2}+ y^{2}- 4x - 2y + 4 = 0$xx_1 + yy_1 - 4\left( \dfrac{x + x_1}{2} \right) - 2\left( \dfrac{y + y_1}{2} \right) + 4 = 0$

$xx_1 + yy_1 - 2(x + x_1) - (y + y_1) + 4 = 0$

$7x_1 - 4y_1 - 2(7 + x_1) - (-4 + y_1) + 4 = 0$

$7x_1 - 4y_1 - 14 - 2x_1 + 4 - y_1 + 4 = 0$

$5x_1 - 5y_1 - 6 = 0$

$y_1 = x_1 - \frac{6}{5}$ ← Equation (2)

Substitute y

_{1}= x_{1}- 6/5 of Equation (2) to Equation (1)${x_1}^2 + (x_1 - \frac{6}{5})^2 - 4x_1 - 2(x_1 - \frac{6}{5}) + 4 = 0$

${x_1}^2 + ({x_1}^2 - \frac{12}{5}x_1 + \frac{36}{25}) - 4x_1 - 2x_1 + \frac{12}{5} + 4 = 0$

$2{x_1}^2 - \frac{42}{5}x_1 + \frac{196}{25} = 0$

$x_1 = \frac{14}{5} ~ \text{and} ~ \frac{7}{5}$

From Equation (2)

$y_1 = \frac{8}{5} ~ \text{and} ~ \frac{1}{5}$

$m = \dfrac{y_2 - y_1}{x_2 - x_1}$

$y - y_1 = m(x - x_1)$

For line L

_{1}$y - \frac{8}{5} = -\frac{4}{3}(x - \frac{14}{5})$

$15y - 24 = -20(x - \frac{14}{5})$

$15y - 24 = -20x + 56$

$20x + 15y - 80 = 0$

$4x + 3y - 16 = 0$

answerFor line L

_{2}$y - \frac{1}{5} = -\frac{3}{4}(x - \frac{7}{5})$

$20y - 4 = -15(x - \frac{7}{5})$

$20y - 4 = -15x + 21$

$15x + 20y - 25 = 0$

$3x + 4y - 5 = 0$

answer## I am happy to register this.

I am happy to register this.